The Use of Adaptive Statistical Iterative Reconstruction in Pediatric Head CT: A Feasibility Study - Vorona, G.A.; Zuccoli, G.; Sutcavage, T.; Clayton, B.L.; Ceschin, R.C.; Panigrahy, A. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Iterative reconstruction techniques facilitate CT dose reduction; though to our knowledge, no group has explored using iterative reconstruction with pediatric head CT. Our purpose was to perform a feasibility study to assess the use of ASIR in a small group of pediatric patients undergoing head CT. MATERIALS AND METHODS: An Alderson-Rando head phantom was scanned at decreasing 10% mA intervals relative to our standard protocol, and each study was then reconstructed at 10% ASIR intervals. An intracranial region of interest was consistently placed to estimate noise. Our ventriculoperitoneal shunt CT protocol was subsequently modified, and patients were scanned at 20% ASIR with approximately 20% mA reductions. ASIR studies were anonymously compared with older non-ASIR studies from the same patients by 2 attending pediatric neuroradiologists for diagnostic utility, sharpness, noise, and artifacts. RESULTS: The phantom study demonstrated similar noise at 100% mA/0% ASIR (3.9) and 80% mA/20% ASIR (3.7). Twelve pediatric patients were scanned at reduced dose at 20% ASIR. The average CTDIvol and DLP values of the 20% ASIR studies were 22.4 mGy and 338.4 mGy-cm, and for the non-ASIR studies, they were 28.8 mGy and 444.5 mGy-cm, representing statistically significant decreases in the CTDIvol (22.1%, P = .00007) and DLP (23.9%, P = .0005) values. There were no significant differences between the ASIR studies and non-ASIR studies with respect to diagnostic acceptability, sharpness, noise, or artifacts. CONCLUSIONS: Our findings suggest that 20% ASIR can provide approximately 22% dose reduction in pediatric head CT without affecting image quality. ACRAmerican College of RadiologyASIRadaptive statistical iterative reconstructionCNRcontrast-to-noise ratioCTDICT dose indexCTDIvolCT dose index volumeDLPdose-length productFBPfiltered back-projectionIRiterative reconstructionIRISiterative reconstruction in image space